METHODE PENGERINGAN AMPAS TEBU (BAGASSE) DENGAN PEMANFAATAN KEMBALI PANAS GAS BUANG BOILER DI PG. PRADJEKAN BONDOWOSO - Solikin, Solikin (Universitas Nahdlatul Ulama Sidoarjo, 2019)
At present the need for fossil fuels is very high, while reserves in nature are decreasing. For this reason, innovation is needed to find alternative energy from fossil fuels to alternative energy that is more environmentally friendly and can be renewed. The sugar factory as one of the Dutch heritage industries that produces solid waste in the form of bagasse can be used for boiler fuel. While the boiler exhaust gas (flue gas) from the chimney generated from burning fuel also causes air pollution can be used for drying bagasse so as to reduce the impact of pollution caused by the exhaust gas.The use of bagasse with a moisture content of around 49 - 52% as boiler fuel as one of the causes of burning in the combustion chamber is not perfect and causes air pollution. The high temperature of the smoke gas coming out through the boiler chimney around 2200C has a heat content of 13475.72 kW and still high levels of water in the pulp can certainly be used to dry bagasse using a dryer (Rotary Dryer) Through the use of flue gas that is wasted on the boiler chimney for bagasse drying, it can increase the heat value of bagasse 50,544 x 106 Kcal / hour for the production of bagasse 30 tons / hour, reduce bagasse water content up to 35,1%, increase thermal efficiency and reduce pollutants released into the surrounding environment.